Biostimulants and their Role in Enhancing Plant Resistance to Pests and Pathogens - Nehul, Janardhan Namdeo; Samreen; Dutta, Anirban; Manjunath, P.; Belagalla, Ningaraj; Kundan; V.B., Gore; Khokale, Sagar Kashinath; Pandey, Shivam Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Biostimulants are natural or synthetic substances that can be applied to plants to enhance their growth, development, and resistance to various stresses, including pests and pathogens. The use of biostimulants in agriculture has gained increasing attention in recent years due to their potential to improve crop yields and quality while reducing the reliance on chemical pesticides and fertilizers. This article provides an in-depth review of the current knowledge on biostimulants and their role in enhancing plant resistance to pests and pathogens. The article discusses the different types of biostimulants, including microbial inoculants, humic substances, seaweed extracts, and protein hydrolysates, and their modes of action in promoting plant growth and defense responses. The article also highlights the potential mechanisms by which biostimulants can enhance plant resistance to pests and pathogens, such as by inducing systemic acquired resistance, promoting beneficial microbial communities in the rhizosphere, and enhancing plant secondary metabolite production. Finally, the article discusses the challenges and future prospects of using biostimulants in sustainable agriculture, including the need for standardization of biostimulant products, optimization of application methods, and integration with other crop management practices. Overall, this article provides a comprehensive overview of the potential of biostimulants in enhancing plant resistance to pests and pathogens and their role in promoting sustainable agriculture.